1984
DOI: 10.1192/bjp.145.4.366
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Cognitive-Behaviour Therapy for Depression in Patients with Multiple Sclerosis

Abstract: Twenty depressed multiple sclerotic patients were randomly allocated either to cognitive-behaviour therapy or to a waiting list control condition. Assessment of depressive symptoms was conducted at pre-treatment, post-treatment, and a four-week follow-up. In comparison to the waiting list condition, cognitive-behaviour therapy was found to result in clinically and statistically significant improvement on most measures. Although the mechanism by which such treatment achieves its effects is unclear, these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 17 publications
3
111
0
2
Order By: Relevance
“…Larcombe and Wilson presented the first results of a group-based CBT trial in patients with MS [105]. Patients were randomly assigned to six weekly sessions of traditional CBT or to a wait-list control group.…”
Section: Group Cognitive-behavioral Therapymentioning
confidence: 99%
“…Larcombe and Wilson presented the first results of a group-based CBT trial in patients with MS [105]. Patients were randomly assigned to six weekly sessions of traditional CBT or to a wait-list control group.…”
Section: Group Cognitive-behavioral Therapymentioning
confidence: 99%
“…Larcombe & Wilson (1984) found that cognitive-behavioural therapy (CBT) for depression was more effective than no treatment. Participants were carefully screened to ensure they met the criteria for definite or probable depression and those with cognitive impairment were excluded.…”
Section: Box 2 Symptoms Of Depression In Multiple Sclerosismentioning
confidence: 99%
“…La declaración describe estudios que han reportado a la TCC, tanto individual como grupal, eficaz en el tratamiento de los síntomas depresivos en la EM (Larcombe 1984;Foley 1987). Las terapias orientadas al insight también se han mostrado de ayuda para la depresión en pacientes internados con EM cuando se las compara con un grupo de control (Crawford 1985).…”
Section: Guías Goldman De Consensounclassified